Activity of arabica green coffee bean (Coffea arabica) extract as an immunomodulator in mice (Mus musculus) infected with Staphylococcus aureus - Aurellia, Sharon; Subangkit, Mawar; Andriyanto, Andriyanto (School of Veterinary Medicine and Biomedical Sciences, IPB University, Bogor, Indonesia, 2024)
Arabica green coffee bean is the most widely produced coffee bean in Indonesia. Studies have shown that arabica green coffee beans are rich in polyphenols and antioxidants, stimulating immune cell proliferation. This study investigated the immunomodulatory activity of arabica green coffee beans (Coffea arabica). Thirty mice (Mus musculus) with an average body weight of 30 g were divided into five groups: negative control, positive control, and groups administered arabica green coffee bean powder extract at doses of 0.03, 0.06, and 0.18 mg/30 g BW. It was orally administered once daily for 14 days. On the 15th day, the mice were intraperitoneally injected with non-pathogenic Staphylococcus aureus. After an hour, mice were necropsied for peritoneal fluid collection. Peritoneal fluid was stained with a peripheral blood smear, and the number of macrophages and lymphocytes was observed under a microscope. Data were analyzed using one-way analysis of variance (ANOVA), followed by Tukey’s test. The group administered with 0.18 mg/30 g body weight (BW) dose showed the highest average of macrophage and lymphocytes compared to the negative control group and any other groups. Arabica green coffee bean powder extract was shown to have immunomodulatory activity, with the highest activity observed at a dosage of 0.18 mg/30 g BW.